Crisis in South American regionalism and Brazilian protagonism in Unasur, the Lima Group and Prosur - Barros,Pedro Silva (2021)
Abstract This paper discusses the crisis in regional governance in South America from 2017 onwards by analyzing Unasur’s disintegration and the emergence of new arrangements (the Lima Group, Prosur, and the Leticia Pact), as well as the regional and global conditions that enabled them. We assessed their performance in responding to different crises in South America, concluding that the constraints and challenges they faced jeopardize their aim to prosper in the future. Special attention is given to changes in Brazilian foreign policy guidelines toward South America, which contributed to these outcomes.